2019
DOI: 10.1016/j.isci.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical 3D Nanoceria Channel for Severe Neurological Defect Regeneration

Abstract: SummaryInflammation and oxidative stress are major problems in peripheral nerve injury. Nanoceria can manipulate antioxidant factor expression, stimulate angiogenesis, and assist in axonal regeneration. We fabricate collagen/nanoceria/polycaprolactone (COL/NC/PCL) conduit by asymmetrical three-dimensional manufacture and find that this scaffold successfully improves Schwann cell proliferation, adhesion, and neural expression. In a 15-mm rat sciatic nerve defect model, we further confirm that the COL/NC/PCL con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Melatonin‐loaded polycaprolactone scaffolds alleviated immune insult and improved repair of a 15 mm long sciatic nerve insult by regulating the autophagy signalling pathway . Three‐dimensional nanoceria‐based nerve conduit and nanodiamond channels also contributed to restoration of immune homeostasis by reducing regional oxidative stress and inflammatory reactions in lengthy sciatic nerve defects . Inflammation and oxidative stress are also responsible for radiation‐induced peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin‐loaded polycaprolactone scaffolds alleviated immune insult and improved repair of a 15 mm long sciatic nerve insult by regulating the autophagy signalling pathway . Three‐dimensional nanoceria‐based nerve conduit and nanodiamond channels also contributed to restoration of immune homeostasis by reducing regional oxidative stress and inflammatory reactions in lengthy sciatic nerve defects . Inflammation and oxidative stress are also responsible for radiation‐induced peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that nanoceria, as a strong self-regenerative antioxidant, can behave as a powerful ROS scavenger to inhibit cell senescence and stimulate neurite sprouting. In 2019, Qian et al evaluated the therapeutic effects of nanoceria in a 3D composite channel for treating a severe neurological defect [ 127 ]. To this end, they incorporated 0.5%, 1%, and 2%–4% nanoceria into a collagen/PCL (COL/PCL) blend to prepare composite conduits by asymmetrical 3D manufacturing.…”
Section: Nanoceria For Soft-tissue Engineeringmentioning
confidence: 99%
“…( B ) Microscopic images exhibiting the triple immunofluorescence of regenerated nerves indicating axonal restoration after 18 weeks of the implantation: A, E, I, and M were stained by DAPI; B, F, J, and N were stained by NF200; C, G, K, and O were stained by Tuj1; and D, H, L, and P show merged images. Reproduced with permission from [ 127 ].…”
Section: Figurementioning
confidence: 99%
“…Fused deposition modeling (FDM) is a printing technology. A temperature-sensitive polymer is heated to a molten state and then deposited on a solid medium through a printing nozzle (Qian et al, 2019). The advantage of this kind of technology is its high precision.…”
Section: Extrusion-based Printingmentioning
confidence: 99%